Tracks of emotion - Luo, Feng, 1964- (Xianggang guo ji shi ge zhi ye 2013., 2013)
Drawn from International Poetry Nights in Hong Kong 2013, Tracks of Emotion is a chapbook of poetry by Natalia Chan presented in English, and Chinese. Tracks of Emotion is also available, along with the chapbooks of other internationally renowned poets, in Islands or Continents (Eighteen-Volume Box Set). Selected poems from this volume are featured in the anthology Islands or Continents: International Poetry Nights in Hong Kong 2013.